Second-Order Neutral Differential Equations with Sublinear Neutral Terms: New Criteria for the Oscillation - Meraa Arab; Hajer Zaway; Ali Muhib; Sayed K. Elagan (Mathematics)
This paper aims to study the oscillatory behavior of second-order neutral differential equations. Using the Riccati substitution technique, we introduce new oscillation criteria that essentially improve some related criteria from the literature. We provide some examples and compare the results in this paper with earlier results to illustrate the importance of our results.